EVALUASI SISTEM DISTRIBUSI AIR MINUM PDAM TIRTA PANCUR AJI SPAMIKK PROJAL KELURAHAN BUNUT KABUPATEN SANGGAU - Jama, Rofinus; Wahyudi, Reza; Zuandi, Weli (Fakultas Teknik Universitas Panca Bhakti, 2022)
Clean water is a source of survival for living things on earth. Bunut Village is one of the villages located in the Kapuas District, Sanggau Regency, West Kalimantan Province, Indonesia located within the Sanggau City area. The background to the lack of equity regarding the distribution of drinking water by PDAM Tirta Pancur Aji at the SPAM IKK Projal service area of Bunut Village is due to the lack of SPAM facilities and infrastructure it affects processing capacity and lacks evaluation of service levels. Therefore, this study aims to evaluate the distribution of drinking water at PDAM Tirta Pancur Aji because every year there is population growth, which affects the level of water demand, the actual conditions regarding the condition of the SPAM IKK Projal have never developed annually, have never evaluated the capacity spam so that the optimization of water distribution to the community has not yet obtained the right strategy for the distribution of drinking water by PDAM Tirta Pancur Aji at SPAM IKK Projal in the Bunut Village Service area. The evaluation of the distribution of PDAM Tirta Pancur Aji water uses population calculations, clean water requirements calculations, and the SPAM IKK Projal strategy to serve the entire Bunut Village community for access to drinking water. Keywords: water distribution, population projection, water demand.